Comparison of penetration performance and penetration mechanism of w-cu shaped charge liner against three kinds of target: Pure copper, carbon steel and Ti-6Al-4V alloy. (November 2016) - Guo, Wenqi; Liu, Jinxu; Xiao, Yao; Li, Shukui; Zhao, Ziying; Cao, Jin
Abstract: In order to investigate the interaction between shaped charge jet and target, three different targets, including pure copper target, carbon steel target and Ti-6Al-4V alloy target, were penetrated by W-Cu shaped charge jet. Penetration performance and corresponding penetration mechanisms were studied. Calculated theoretical penetration depth ratio of Ti-6Al-4V alloy target, pure Cu target and carbon steel target is 10:2.8:5.7, while the practical penetration depth ratio is 10:28:21, indicating that the interaction between jet and target has a significant effect on the penetration depth. Microstructural analysis shows that the interaction between jet and Cu target is the lightest among the three kinds of targets, leading to an increased penetration depth of Cu target. The interaction between jet and Ti-6Al-4V alloy target is the severest, resulting in an increased transverse energy dissipation of jet and decreased penetration depth of Ti-6Al-4V alloy target. Given the significant interaction between jet and target, we propose a modified equation of penetration depth by adding an empirical parameter, which provides a platform to predict more accurate penetration depth. Highlights: Penetration performance and penetration mechanism of W-Cu shaped charge jet against three targets were investigated. Interaction between shaped charge and targets was revealed. A modified equation of penetration depth considering the effect of interaction between jet and target is proposed.